A Systematic Review of Branding Strategies and Their Impact on Consumer Loyalty of Sharia Banking - Nada Cantika Putri Kadua; Muhandis Difa’iy Aziz (PT. Anagata Sembagi Education, 2026)
This study aims to systematically review branding strategies and their impact on consumer loyalty in Sharia banking institutions. Using a Systematic Literature Review (SLR) with the PRISMA approach, this research analyzes peer-reviewed articles published between 2020 and 2025, resulting in seven key studies selected for in-depth examination. The findings indicate that branding strategies in Sharia banking—particularly those related to brand trust, brand image, corporate reputation, service quality, and Sharia compliance—play a significant role in shaping consumer loyalty, both attitudinal and behavioral. Moreover, emotional factors and perceived ethical values are found to strengthen the relationship between branding efforts and customer loyalty. This study contributes to the existing literature by synthesizing recent empirical evidence on Sharia banking branding and provides practical implications for bank management in designing effective branding strategies to enhance sustainable consumer loyalty.